Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyń Influence of low energy laser irradiation on hemodynamic parameters of isolated perfused rat’s heart subjected to ischaemia – preliminary data - Biały, Dariusz; Skrzypiec-Spring, Monika; Arkowski, Jacek; Wawrzyńska, Magdalena; Grotthus, Bartosz; Kwiatkowska, Joanna; Szeląg, Andrzej; Mazurek, Walentyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Laser irradiation can modulate biological processes. Its influence on the processes taking place in heart muscle during ischaemia seems to be of particular importance. Aim: Analysis of influence of low-energy laser irradiation on hemodynamic parameters of perfuse rat’s hart subjected to ischaemia. Material and methods: Isolated rat hearts perfused with Krebs-Hanseleit solution were subjected to 20 minutes ischaemia. During the ischaemia some of the hearts were irradiated with low energy laser. Results: The hearts which were irradiated with laser during ischaemia showed better hemodynamic function (rate pressure product – RPP) compared to the hearts that were not irradiated. Conclusions: Low energy laser irradiation has a positive influence on hemodynamic function of isolated rat’s heart subjected to ischaemia.